Urban noise classification for active noise control in residential buildings - Teng, Meng Yong (Nanyang Technological University, 2021)
In this report, a microphone array will be designed for an Active Noise Control (ANC) system. A microphone pre-amplifier circuit will also be created and implemented in this ANC system, with the goal of sufficiently amplifying mic level voltages to line level voltages for further processing by the ANC system. This circuit will then be implemented on a printed circuit board. Based on tests conducted on this circuit, gain performance has been found to be as expected theoretically without significant degradation. However, noise and distortion levels in the circuit were found to be not as low as expected.